2002
DOI: 10.2166/ws.2002.0094
|View full text |Cite
|
Sign up to set email alerts
|

Automated event sampling for microbiological and related analytes in remote sites: a comprehensive system

Abstract: Pathogen concentrations are most often monitored during dry weather. Generally in Australia, however, loads mobilised during storms are of more concern. The filling of reservoirs commonly occurs from heavy rain events, and flood inputs may destabilise reservoir hydraulics leading to short-circuiting of contaminates to water supply off-takes. To capture storm events that can occur rapidly in remote locations at any time, automated sampling would seem appropriate. Unfortunately no commercial sampling system appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…This confirms a previous report that microbiological cross contamination or carry over for faecal indicators (FI) from corresponding previous sampling cycles are expected below 2%, if dead zones are removed and flushing cycles before each sampling interval are to be applied (Roser et al 2002). However, the automated microbial sampling could be improved by cooled sampling devices, although the surrounding temperature in the spring tapping of our monitored springs was not appreciable higher as the water temperature (approximately 5.5°C) during summertime.…”
Section: Discussion and Further Developmentssupporting
confidence: 89%
See 1 more Smart Citation
“…This confirms a previous report that microbiological cross contamination or carry over for faecal indicators (FI) from corresponding previous sampling cycles are expected below 2%, if dead zones are removed and flushing cycles before each sampling interval are to be applied (Roser et al 2002). However, the automated microbial sampling could be improved by cooled sampling devices, although the surrounding temperature in the spring tapping of our monitored springs was not appreciable higher as the water temperature (approximately 5.5°C) during summertime.…”
Section: Discussion and Further Developmentssupporting
confidence: 89%
“…Additionally, the described system is not limited to E.coli as a general parameter of recent faecal pollution and may thus be extended to other appropriate microbial indicators and tracers. In this case, modification may be necessary in order to increase and adapt required sampling storage volumes (Roser et al 2002). …”
Section: Discussion and Further Developmentsmentioning
confidence: 99%
“…It could therefore be hypothesised that this indicator needs a high rainfall intensity to be mobilised. Events 2 and 4 are also preceded This is similar to findings reported by Roser et al (2002).…”
Section: Event Analysissupporting
confidence: 89%
“…Capturing a storm in this way could provide an indication as to whether there is a flush of contaminants from the catchment, as is reported in urban storm water literature (Lee et al 2002;Taebi & Droste 2004), or whether once mobilised there is a seemingly endless supply of pollutants, as reported by Roser et al (2002). This sampling regime is similar to the sampling regime in event 1.…”
Section: Event Analysismentioning
confidence: 76%
“…This deficiency can potentially lead to false-negative results or underestimation of (10)(11)(12)(13). Nonetheless, several studies have demonstrated the potential of automated sampling procedures for pollution microbiology (2,(14)(15)(16)(17). For example, autosampling was used to elucidate previously unobserved microbial fecal pollution dynamics in alpine water resources, results that had significant implications for water quality management (14,18).…”
mentioning
confidence: 99%